THE MEAN LIGHT CURVES OF THE MIRA-TYPE STARS IN THE H- AND K-BANDS - Kudashkina, L. S. (Одеські астрономічні публікації, 2016)
. For nine Mira-type stars (o Cet, R Leo, S Car, U Her, X Oph, R Aql, RR Aql, S Ori, S Scl,) and one semi-regular star (L2 Pup), the mean light curves have been obtained. The initial values of the brightness (observations) were fitted by a trigonometric polynomial of the statistically optimal order.The Fourier coefficients and the additional parameters (degree of the trigonometric polynomial, amplitude of the brightness, the maximal slope of ascending and descending branch, semi-amplitudes and initial epochs for the brightness maximum (minimum magnitude) of each harmonic contribution, etc., were given in the tables reported earlier by Kudashkina (2016). In this study, we have received several interesting correlations between these parameters in the bands H and K. It was particularly noted the anomalous position on the figures of the star X Oph.The mean light curves of the investigated stars are commonly symmetric in the near infrared region (H and K). Stars: Pulsating: Mira-type: SR